Enhancing Vinasse Treatment Efficiency using Electro-Fenton: The Role of Electrode Thickness and Power Supply Voltage - Lilik Suprianti; Friska Nur Cahyani; Andreas Deardo HP; Kindriari Nurma Wahyusi; Nindia Noor Indah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The production of ethanol from molasses generates vinasse as a by-product of the distillation process. Vinasse waste produced by PT Energi Agro Nusantara contains COD and BOD levels of 910.5 ppm and 460.5 ppm, respectively, which significantly exceed the maximum limits set by wastewater quality standards, necessitating treatment. One treatment method is the use of Advanced Oxidation Processes (AOPs), which utilize hydroxyl radicals to oxidize organic pollutants in vinasse. One such process is the electro-Fenton process. In this study, 500 ml of vinasse was placed in a beaker and stirred for 90 minutes. A 25 ml addition of hydrogen peroxide was made, with a 2 cm gap between the iron electrode plates. Voltage variations of 3V, 6V, 9V, and 12V, along with electrode thicknesses of 2 mm, 3 mm, 4 mm, 5 mm, and 6 mm, were tested. COD and BOD levels were analyzed using the titrimetric method. The results showed that increasing the voltage and electrode thickness reduced COD and BOD levels, while the percentages of COD and BOD removal increased. The highest voltage (12V) and electrode thickness (6 mm) yielded the lowest final COD and BOD values of 163.5 ppm and 88.9 ppm, respectively, with COD removal at 82% and BOD removal at 81%.